(untitled) (Research, Society and Development, 2020)
Objective: The present study evaluated the knowledge and behaviors after accidents with perforating instruments of all the dentists of the Basic Units of Family Health of the city of Sousa/PB. Methodology: A questionnaire containing objective questions was applied to investigate the prevention measures and behaviors after the drilling accident among the participants of the research. All data were analyzed and conducted using SPSS Statistics software version 20.0 and considering a 95% confidence interval. Results: The results showed that most dental surgeons have already had an accident handling perforating instruments, in a higher percentage due to lack of attention and the most used conduct after the accident was hand washing with soap and water. There was no statistically significant difference between the male and female groups with the occurrence of perforating accidents among dentists (p-values ≥0,05). Conclusion: Despite the adoption of basic Biosafety measures, the percentage of perforation accidents with potential for biological contamination is still high, making it necessary to implement more measures to prevent accidents and preserve the health of dentists and staff.